(3EjVGM ThGgO GdEjVGMs - (3CHhYdj GdMSf Hf YHO Gddg GdbjSj GdeZQHjs; (3CHh Ydj GdaGQSj , GdMSf Hf CMeO Hf YHO GdZaGQ Hf eMeO Hf SdjeGf, CHh Ydj,J (B377 (3g` s
(3ChdgG (B:s
(3CeG HYO, aEfc SCdJfj Cf CTQM dc ThGgO cJGH GdEjVGM dCHj Ydj GdaGQSj s
(3BNQgG (B:s
(3ef CHjGJ dCHj GdCShO hdcf EPG eG GSJLeYG YfO hGMO aMb dg ef WGYmI HfUjH s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs